PENGARUH E-FILING, PENGETAHUAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA JAMBI PELAYANGAN - Dhafi Ammar Junaidi; Agustina Mutia; Eri Nofriza (EKSYA : Jurnal Ekonomi Syariah, 2024)
The purpose of this study was to determine the impact of E-filing, Knowledge and Tax Sanctions on Individual Taxpayer Compliance at the Jambi Pelayanangan Pratama Tax Office. This study uses a quantitative approach using multiple regression statistical analysis methods partially and simultaneously to determine the effect of E-filling (X1), knowledge (X2), and Tax Sanctions (X3) on Taxpayer Compliance. The research conducted produced the following findings and conclusions: This study concludes that E-filling has a negative effect on individual taxpayer compliance, while knowledge has a negative effect on individual taxpayer compliance, and Tax Sanctions have a positive effect on individual taxpayer compliance. T-test Based on the results of multiple regression tests, it can be concluded that the t-value for E-filling is -3.418 < t table 1.984 and a Sig value of 0.001 < 0.05. While the Knowledge variable (X2) gets a t-value of -5.069 < t table 1.984 and a Sig value of 0.000 < 0.05. Then the Tax Sanctions variable (X3) gets a t-value of 6.375 > t table 1.984 and a Sig value of 0.000 < 0.05. Simultaneously (F test) shows that the independent variables E-filling, Knowledge and Tax Sanctions together or simultaneously affect taxpayer compliance at the Jambi Pelayanangan Pratama Tax Office. Partially, the independent variables that have a significant influence are Tax Knowledge, Tax Sanctions, and the Implementation of E-Filling have an influence on taxpayer compliance.